SLM is Dead, Long Live Sri Lanka Malay: A Review Article of Nordhoff 2013 - Ansaldo, Umberto (2014)
This paper discusses the results of scholarship on Sri Lanka Malay based on the studies presented in Nordhoff 2013 in terms of theory, method, and social impact. It touches on a variety of topics including the significance of recent genetic evidence for old theories of language genesis, as well as the efforts for revitalization sparked by the scientific interest in the speech community. In evaluating this collection of variable significance, the author reflects on the transition of ownership of Sri Lanka Malay: from object of scientific curiosity to ancestral language of communal value.